KEPEMIMPINAN GURU DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PAI - Nasution, Khalilah (IAIN Padangsidimpuan, 2016)
The leadership of teacher is an action taken by the teacher in influencing, directing, motivating, guiding in leading students to achieve the desired objectives in order to create learning effectiveness. The leadership of the teacher should be able to master the teaching materials, love to teach, having and knowing personal experience and knowledge of the students, has a variety of methods, if the teacher teaching should always provide the knowledge of actual and preparation as well as possible, teachers should be in bold to give such praise to the students, a teacher must be able to raise the spirit to learn individually for learners. The leadership of the teacher could boost the effectiveness of learning in accordance with the expected by the teacher.